Quantitative techniques - Lucey, T. (London : Continuum, 1996)
This introductory interdisciplinary textbook covers all the major topics involved at the interface between business and management on the one hand and mathematics and statistics on the other. Topics dealt with include logistics, finance, production and operations management, and economics. It is especially relevant to students studying quantitative techniques as part of business, management and/or finance on undergraduate and professional courses, especially: ACCA; CIMA; CIPFA; ICA, IOB, ICAEW.
Includes index.
oif 11/08/15
Loan
Keywords: Business mathematics; Accounting; Quantitative techniques; Operations research; Management science